PENGARUH CURRENT RATIO, TOTAL ASSET TURNOVER, DAN DEBT TO EQUITY RATIO TERHADAP RETURN ON ASSET PADA PERUSAHAAN SUB SEKTOR MAKANAN DAN MINUMAN YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) PERIODE 2018-2022 - Michela, Adezia Zefanya; Tatyana, Tatyana; Artini, Ni Made; Hendriyani, Mungky (Institut Teknologi dan Bisnis Swadharma, 2024)
This research aims to examine the impact of the Current Ratio, Total Asset Turnover, and Debt to equity ratio on Return On Assets, and the combined impact of Current Ratio, Total Asset Turnover, and Debt to Equity Ratio on Return On Assets in companies operating in the Food and Beverage sub-sector listed on the Indonesia Stock Exchange (BEI) from 2018 to 2022. The population for this research comprises all food and beverage sub-sector companies listed on the IDX. A sample of 10 food and beverage sub-sector companies listed on the IDX was selected using purposive sampling. A secondary data collection technique was employed for this research. The data was analyzed using a quantitative approach and techniques such as the Classical Assumption Test, Multiple Linear Regression, t-test and F Test, and Coefficient of Determination. The data management utilized the SPSS 29 software program. The findings of this research demonstrate that the Current Ratio significantly impacts Return on Assets, Total Asset Turnover does not have a significant effect on Return On Assets, Debt To Equity Ratio significantly affects Return On Assets, and that Current Ratio, Debt To Equity Ratio, and Total Asset Turnover collectively have a significant impact on Return On Assets.Tujuan penelitian ini adalah untuk menguji dan menganalisis pengaruh current ratio terhadap return on asset, pengaruh total asset turnover terhadap return on asset, pengaruh debt to equity ratio terhadap return on asset, dan pengaruh current ratio, total asset turnover, dan debt to equity ratio terhadap return on asset pada perusahaan sub sektor makanan dan minuman yang terdaftar di Bursa Efek Indonesia (BEI) periode 2018-2022. Populasi dalam penelitian ini adalah seluruh perusahaan sub sektor makanan dan minuman yang terdaftar di BEI. Sampel dalam penelitian ini ditentukan menggunakan purposive sampling dengan total berjumlah 10 perusahaan. Teknik pengumpulan data dalam penelitian ini menggunakan data sekunder. Teknik analisis data menggunakan pendekatan kuantitatif. Teknik analisis data dalam penelitian ini menggunakan Uji Asumsi Klasik, Regresi Linear Berganda, Uji t dan Uji F, dan Koefisien Determinasi. Hasil penelitian ini membuktikan bahwa Current Ratio berpengaruh signifikan terhadap Return On Asset, Total Asset Turnover tidak berpengaruh signifikan terhadap Return On Asset, Debt To Equity Ratio berpengaruh signifikan terhadap Return On Asset, dan Current Ratio, Debt To Equity Ratio Dan Total Asset Turnover berpengaruh signifikan terhadap Return On Asset